TARIXIY-MOLIYAVIY RAMZLARNI NAMOYISH ETISH ORQALI FIZIKA MASHG’ULOTLARI SAMARADORLIGINI OSHIRISH - Yavidov, B.Ya.; Otajonova, M.R. (SCIENCE and SOCIETY, 2019)
The article deals with one of the methods for increasing the effectiveness of classes in Physics. To improve the efficiency of classes in Physics, it is proposed to use a new teaching method - the method of “demonstrating historico-financial symbols”. The principle of the method is to demonstrate the historico-financial symbols (banknotes), in which physicists-scientists are depicted in the study of physical phenomena and the laws related to their names. The method can be applied in lectures, practical and seminar lessons in physics.
Keywords: Physics; teaching methods; historical and financial symbols